Use of Sodium Hypochlorite for Skin Antisepsis Before Inserting a Peripheral Venous Catheter: A Pilot Study. (May 2015) - Forni, Cristiana; Sabattini, Tania; D'Alessandro, Fabio; Fiorani, Ambra; Gamberini, Simonetta; Maso, Alessandra; Curci, Rosa; Zanotti, Enrichetta; Chiari, Paolo
Although it can be prevented, catheter-related bacteremia is common and dangerous. The antiseptics most widely used during insertion of peripheral venous catheters (PVCs) include povidone iodine, alcohol, and chlorhexidine. Another widely used antiseptic is a solution of 0.057 g sodium hypochlorite. This pilot study explored the contamination rate of the PVC tip inserted after skin decontamination with sodium hypochlorite. Culture analysis of the tips of the PVCs inserted into the 42 participants showed 7 (16.7%) colonized catheters. The results of this pilot study suggest taking into serious consideration the assessment of this antiseptic in randomized experimental studies.